A new species of the genus Halicyclops (Copepoda, Cyclopoida, Cyclopidae) from freshwater in Central Vietnam - Luong, Tran Duc; Minh, Le Danh; Hai, Ho Thanh (Academia Journal of Biology, 2017)
A new cyclopoid species belonging to the genus Halicyclops, H. songsonensis sp. nov. is described from freshwater in Son river, Quang Binh province, Central Vietnam. The new species is distinguished from the other congeners species of the genus by a combination of the having 3:4:4:3 spine formula on P1-P4, lateral angular protuberances on the genital double-somite, a serrate hyaline frill of pre-anal somite little more developed than lateral and ventral parts, relatively long caudal rami, spiniform seta of proximalmost seta on P2-P3 Enp3 and showing the round/oval integumental window on cephalothorax and two next prosomites.